The role of laparoscopic radical prostatectomy in the era of robotic surgery - Rassweiler, Jens; Hruza, Marcel; Klein, Jan; Goezen, Ali S.; Teber, Dogu (European urology. Supplements, 2010)
Context - In the United States, >70% of all radical prostatectomies are performed by use of the da Vinci robot. In Europe, laparoscopic radical prostatectomy (LRP) still plays a significant role. - Objective - To evaluate the actual and future position of LRP based on the current literature and personal experience with robotic and laparoscopic radical prostatectomy. - Evidence acquisition - PubMed and Medline were used to review the recent literature focusing on ergonomic aspects, marketing, and current functional and oncologic results of both procedures as well as of the open counterpart. - Evidence synthesis - The advantages of robot-assisted laparoscopic prostatectomy (RALP) are mainly related to ergonomic aspects of the procedure, such as the sitting position of the surgeon and the clutch function that enables comfortable handling of the manipulators. Laparoscopic surgery would benefit from significant improvements in ergonomics, such as a chair for the surgeon, specially designed operating room tables, and ergonomically designed instrument handles. Future modifications of the laparoscopic technique, such as a single-port surgery (eg, laparoendoscopic single-site surgery [LESS]), may also have an impact on the application and use of LRP. - Conclusions - RALP is here to stay mainly due to improved ergonomics resulting in a shorter learning curve. Ergonomics of laparoscopy require significant improvement, including the design of new operating room tables, supports for the surgeon with integrated foot pedals, mobile high-definition television monitors, and new instrument handles to minimise mental and physical stress. Implementing the latter to such new approaches as LESS will close the gap between robot-assisted and pure laparoscopic surgery.
Gesehen am 10.05.2023